Diseño técnico de un sistema de cuantificación de metano portable y de bajo costo - Tovar-Sánchez, Juan Andres; Arias-Molina, Juan Francisco; Milquez-Sanabria, Harvey Andrés; Mayorga-Castellanos, Manuel Alejandro (Ingeniería, 2023)
Context: Based on an analysis of the development of biodigester technology, a recurring problem with the rigorous quantification of methane was observed. A bibliographical review evidenced systems that are inefficient or have high costs. This work proposes an accessible and effective system that seeks to contribute to related academic and research projects. Method: Methane quantification is used an MQ-4 series sensor coupled with a capsule, thus creating a partially closed medium in which a dilution of sample gases and ambient air is injected by using a syringe, thus extending the measurement range of the sensor. Results: A calibration curve was elaborated, extending the measurement range from 0,02-1% concentration to 10-80%v/v, with a variance of ± 5%. Conclusions: An efficient and accessible prototype for methane quantification for academic and re- search purposes was developed. A guide for replicating the process is added as a complement.